Integrated Effect of Rhizobium Inoculation and Phosphorus Application on Tissue Content, Symbiotic and Phosphorus use Efficiency in Soybean Production - Mulambula, S; Gathungu, G. K; Ndukhu, H.O; Ogolla, F.O (International Journal of Environment, Agriculture and Biotechnology, 2019)
Soybean (Glycine max) is an important legume crop that is cultivated all over the world as livestock feed, food for human consumption, soil fertility improvement and industrial products such as candles and paints. However, Nitrogen (N) and phosphorus (P) nutrient have been attributed to the decline in soybean yields. Furthermore, scanty information is documented on P-efficient soybean genotypes, which are a sustainable P management strategy for enhancing symbiotic efficiency(SEF) and phosphorus use efficiency (PUE). As a solution, field experiment was conducted at Chuka University farm to evaluate the integration effect of rhizobium inoculation (R) and P on tissue nutrient content, SEF and PUE in soybean production in Meru South Sub County. Two cultivations (Trial I and II) were done in 2018.Treatments included; three rates of R (0, 100 and 200 g ha-1), three rates of P (0, 20 and 30 kg- ha-1), either applied alone or integrated and soybean genotypes (SB19 and SB24). Both Trials were laid out in a randomized complete block design in split-split plot arrangement with each treatment replicated thrice. Genotypes were assigned main plot, R subplots and P in sub-subplots. Data collected was subjected to analysis of variance using the Scientific Analysis System SAS and significantly different means separated using Tukeys test at(p≤0.05). The results showed significant difference in N and Ptissue content, SEF and PUE for SB19 and SB24 genotypes in both Trials at(p≤0.05). The highest N tissue content of between 1.73% and 9.10% was observed when integration of R and P were applied at the rate of 200 g and 30 kg for SB19 and SB24 in both Trials. While R and P at the rate of 200 g and 30 kg per ha showed the highest P content of between 849.6 ppm and 955.0 ppm in both Trials. The highest SEF recorded was 207% and 261%, and 201% and 227% in Trials I and II, respectively. The PUE was highest when R and P was applied at the rate of 200 g and 30 kg per ha for SB19 and SB24 soybean in both Trials. Integration of R and P at the rate of 200 g and 30 kg ha-1 and adoption of either SB19 or SB24 showed a potential in enhancing soybean cultivation.